1992
DOI: 10.1136/oem.49.1.66
|View full text |Cite
|
Sign up to set email alerts
|

A report of two cases of chronic serious manganese poisoning treated with sodium para-aminosalicylic acid.

Abstract: Two cases of chronic manganese poisoning were treated with sodium para-aminosalicylic acid (PAS-Na; 6 g/day in 500 ml of 10% glucose solution by intravenous drip). The results indicated that one had been clinically cured and that the other had obviously improved in clinical symptoms and signs. Thus PAS-Na appears to be an effective drug for treatment of serious chronic manganese poisoning.Sodium para-aminosalicylic acid (PAS-Na) is a drug used in the past for treating tuberculosis. Its pharmacology was studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 1 publication
0
48
0
Order By: Relevance
“…Neurological signs seem to reach a plateau after an initial 5-10 years of progression (Huang et al 2007), but this observation is based on the follow up of four patients only. However, it has been documented, in a few cases and in uncontrolled studies (Discalzi et al 2000;Herrero Hernández et al 2003;Herrero Hernández et al 2006;Ky et al 1992;Ono et al 2002;Penalver 1957;Tuschl et al 2008) that manganism can be reversed if promptly diagnosed and treated with chelating drugs. Manganism frequently appears in young, active workers.…”
Section: Clinical Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurological signs seem to reach a plateau after an initial 5-10 years of progression (Huang et al 2007), but this observation is based on the follow up of four patients only. However, it has been documented, in a few cases and in uncontrolled studies (Discalzi et al 2000;Herrero Hernández et al 2003;Herrero Hernández et al 2006;Ky et al 1992;Ono et al 2002;Penalver 1957;Tuschl et al 2008) that manganism can be reversed if promptly diagnosed and treated with chelating drugs. Manganism frequently appears in young, active workers.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Early studies lacked detailed information on treatment and biomarkers, and other drugs were coadministered, thus potentially confounding the results. Recent work (Hazell et al 2006) has also shown that the Mn chelator 1,2-cyclohexylenedinitrilotetraacetic acid (CDTA) blocked the development of pathological changes in glial cells of rats treated with MnCl2PAS-Na, an antitubercular and antiinflammatory drug, has also been suggested to be useful in occupational manganism (Jiang et al 2006;Ky et al 1992), but the patient with the longest follow-up was also previously treated with CaNa2EDTA (Jiang et al 2006). PAS-Na has been reported to actually increase brain Mn concentrations in MnCl2 poisoned rodents (Sánchez et al 1995).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…PAS treatment significantly reduced Mn levels in soft tissues (liver, heart, spleen and pancreas) and brain (striatum, thalamus, choroid plexus, hippocampus and frontal cortex) of Mnexposed rats by 16 to 33% (Zheng et al, 2009). PAS-Na, as an analogue of PAS, has been used successfully in the treatment of manganism with a good prognosis (Ky et al, 1992;Jiang et al, 2006), these were subsequently coordinated by other in vivo studies (Yoon et al, 2009;Li et al, 2015). The present study showed that PAS-Na treatment restored Mn-induced cell injury, cell viability reduction and DNA damages in basal ganglia astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sodium para-aminosalicylate (PAS-Na), an analogue of PAS, was found to be effective in clinical treatment of manganism (Ky et al, 1992;Jiang et al, 2006). However, the mechanism of PAS-Na protection against Mn-induced neurotoxicity is unclear.…”
Section: Introductionmentioning
confidence: 99%